Isolated neurosarcoidosis presenting with multiple cranial nerve palsies - Shimizu, Kiyoharu (Surg Neurol Int, 2016)
BACKGROUND: As an extremely rare subtype of sarcoidosis that develops exclusively in the nervous system, isolated neurosarcoidosis is difficult to diagnose. In addition, its exact clinical features are not known. CASE DESCRIPTION: A 61-year-old man presented with right ear hearing loss, diplopia, and fever. Computed tomography (CT) and magnetic resonance imaging revealed mass lesions in the right cerebellum and left side body of the lateral ventricle. Neither systemic CT nor positron emission tomography revealed extracranial lesions. A neuroendoscopic biopsy was performed on the lateral ventricle lesion, and a histopathology analysis revealed epithelioid granulomatous inflammation. By systematic exclusion of other possible granulomatous diseases, isolated neurosarcoidosis was diagnosed. The lesions disappeared immediately upon corticosteroid (methylprednisolone) treatment and had not recurred as of a 12-month follow-up examination. CONCLUSIONS: Isolated neurosarcoidosis is difficult to diagnose. Successful diagnosis requires compatible clinical findings, histological demonstration of noncaseating granulomas, and exclusion of other granulomatous diseases. Isolated neurosarcoidosis has a relatively good clinical prognosis, which could be characteristic of the disease.